Innovation Platform for Improving Rice Marketing Decisions Among Smallholder Farmers in Homa-Bay County, Kenya - Ouma, Matilda A.; Onyango, Christopher A.; Ombati, Justus M.; Mango, Nelson (Taylor and Francis Online, 2020)
Smallholder farmers are normally faced with making a decision on market participation and consequently choosing the appropriate marketing channel for their agricultural produce. This study focuses on how a multi-stakeholder innovation platform approach for improving the uptake of System of Rice Intensification and rice productivity influences marketing decisions among smallholder rice farmers. The study relies on primary data collected from 102 households in Homa-Bay County, Kenya. Logistic and multinomial logistic regression models were used in the analysis. The practice of system of rice intensification, membership to farmer groups, frequency of access to extension services, distance to the nearest market and access to transportation facilities were important determinants to market participation among farmers. A farmers’ choice of marketing channel was commonly influenced by size of land under rice cultivation, access to transport facilities and whether rice was to be sold collectively or individually. We therefore conclude that the multi-stakeholder innovation platform approach improves decision making in marketing. We thus recommend that governments embrace multi-stakeholder Innovation Platforms as a framework for improving farmer participation in rice markets and improving decision making when approaching available markets.
Keywords: Innovation Platform; Market Participation; Rice; Decision Making; Kenya